THE CRITICAL ROLE OF TECHNOLOGY ADOPTION AND COMPETENCY THROUGH IMPROVING TEAMWORK AND KNOWLEDGE TRANSFORMATION IN THE FURNITURE BUSINESS IN JEPARA - Silviana, Amanda; Pudjiarti, Emiliana Sri (STIE Pelita Nusantara Semarang, 2024)
The Jepara furniture industry, facing global pressure and intense competition, must integrate technology and increase competence to maintain competitiveness. This article analyzes the critical role of technology adoption and competency development through improving teamwork and knowledge transformation in the context of the furniture business in Jepara. Using quantitative research methods and conducting surveys on furniture companies in Jepara, data was analyzed through questionnaires that focused on critical variables, such as technology adoption, teamwork, knowledge transformation, and business competency indicators. The research results show that technology adoption, improved teamwork, and knowledge transformation positively correlate with business competency. Technology integration provides operational efficiency, while improved teamwork and knowledge transformation improve employee skills and response to market dynamics. This article provides insight into the importance of this strategy in creating an efficient and responsive business model in the Jepara furniture industry. The practical implications include guidance for furniture business players to increase competitiveness through technology adoption, strong teamwork and effective knowledge management.